Connections between Online International Learning and Inclusion of Intercultural and International Elements in the Curriculum-The Perspective of Slovene Academics - Katarina Aškerc Zadravec (MDPI AG, 2023)
Online international learning and the inclusion of intercultural and international dimensions in the curriculum are closely connected concepts, not only in theory but also in strategic documents and teaching practice. This article presents statistical connections between online international learning and the inclusion of intercultural and international dimensions in the curriculum, based on a survey that included 1367 Slovene academics (19.7% of the entire population). According to the χ2 and Mann-Whitney tests, it was determined that academics who actively include students in any kind of online international learning with institutions from geographically distant areas, and those academics who consider the ICT support at their home institutions as satisfactory for the implementation of online international learning, statistically significantly more often incorporate international and intercultural elements into the study process, covering internationalised learning outcomes, internationalised learning and teaching activities, and internationalised assessment and evaluation tasks.